Virtual education in the rural sector: analysis of scientific literature - Valencia-Arias, Alejandro; Méndez Velásquez, Lina Marcela; Agudelo-Ceballos, Erica; Cumpa Vásquez, Jorge Tomás; Jimenez Garcia, Jesus Alberto; Martínez Rojas, Ezequiel (Frontiers in Education, 2025)
IntroductionThe advent of the pandemic has led to a surge in the popularity of virtual education in rural areas, offering the potential to bridge the access gap. Despite the opportunities provided by digital transitions, challenges persist in regional educational events, requiring differentiated approaches. The lack of accurate information justifies the need for research, particularly to analyze and address neglected areas. This study aims to explore research trends in the field.MethodsA bibliometric analysis was conducted following the PRISMA-2020 statement, using data from the Scopus and Web of Science databases.ResultsThe findings indicate exponential growth in research, with 2021 and 2022 being the most prolific years. Key references include the author Wang J, the journal Computers & Education, and leading research contributions from the United States and India. Thematic evolution suggests a shift towards topics such as professional learning, mental health, and public health. The keyword co-occurrence network highlights thematic clusters related to e-learning, information and communication technology (ICT), and teacher training.DiscussionThe analysis of keyword validity and frequency reveals emerging concepts like rural health and digital inclusion, alongside established themes such as education. This study provides a detailed understanding of the research landscape on virtual education in rural areas, identifying areas of interest and emerging trends.